The effect of using Audio Visual Chat on seventh grade students' oral skills in Jordan and their attitudes toward it - Al- Rawashdeh, Khetam Abd Al- Rahman (Journal of Educational and Psychological Sciences, 2021)
This study aimed to examine the effect of audiovisual chat on seventh grade students English foreign language (EFL) learners’ oral skills. It also investigated the seventh grade students' attitudes toward using audiovisual chat in teaching and learning oral skills in English. The study participants consisted of 32 seventh grade female students from Al Khanasiri Mixed Elementary School at Al- Mafraq, North West Badia Region during the first semester of the scholastic year 2020/2021. The study's participants were divided into two groups: The first group was experimental consisted of (16) students who used the audiovisual chat and the second group was a control one consisted of (16) students who were submitted to regular instruction. To carry out this study, two instruments were used which were the pre- test and post- test. They were of two parts: a speaking and reading test that examined students’ ability to interact appropriately in communicative settings and a questionnaire.To measure the effects of audiovisual chat on the seventh grade learners’ oral skills, before beginning the experiment, both groups will take a speaking and reading test to measure their existing awareness at the start of the first semester of the academic year 2020/2021. The study's findings show that the experimental group performed better in the oral ability than the control group, due to this new teaching approach that incorporates audiovisual chat. The study's findings reveal that the experimental group is more inspired than the control group. This is due to the effect of using audiovisual chat. Accordingly, a number of conclusions and recommendations are provided.
Keywords: Effect; audiovisual chat; oral skills; attitude